Psychological distress of inmates at a women's prison in Lima after the first wave of COVID-19 in November 2020 - Silvia Esteban-Febres; Santos Guzmán-Gamarra; Melisa La Cunza-Peña; Yovana Quispe-Gutiérrez (Sociedad Española de Sanidad Penitenciaria, 2023)
Abstract Objectives: A descriptive study was carried out to establish the levels of psychological distress amongst female inmates at a high-security prison in Lima in November 2020, after the first wave of COVID-19. Material and method: The Brief Symptoms Inventory-18 (BSI-18) was applied to a representative sample of 314 female inmates who agreed to participate in the study. Results: Results showed that 34.6% of the inmates could be considered as cases of psychological distress. Moreover, the depression subscale had the highest score, followed by the anxiety and the somatisation subscales. The most prevalent symptom was "feeling blue". Discussion: The prevalence of distress symptoms was analyzed, taking into account the effects of the first wave of COVID-19, the suspension of family visits, the restriction of treatment and leisure activities, etc. Gender aspects were also taken into consideration.